Abstract Concepts, Language and Hybridism - Martínez Manrique, Fernando (Analysis. Journal of Philosophical Research, 2020)
The topic of this paper is the problem of abstract concept grounding, i.e., how they can be grounded in experience. I argue that, even if modal, embodied approaches can refer concept acquisition to distinct types of world experiences, they still have a problem accounting for the suitable mental representations that articulate them. I will offer a brief panoramic of treatments of abstract concepts in some contemporary theories that I will divide into two groups: unitary and pluralistic. Even though current research points towards pluralistic approaches as the most plausible ones, there is still a problem to explain how the plurality of representations are combined. I will present this in terms of the combination of concrete and abstract concepts. I will argue that, in contrast to the abstract-to-concrete strategy, a concrete-to-abstract strategy is possible. This strategy may be well in accordance with the nature of abstract properties themselves.